Evaluation of diesel fuel production from bio-oils hydrodeoxygenation using unsupported MoS2 catalysts - Yi Zhang; Jacques Monnier; Philip Bulsink; Moataz Abdrabou; Jian Li; Xin Pang; Nafiseh Zaker; Rafal Gieleciak (Fuel Processing Technology, 2025)
Diesel production from lignocellulosic biomass-derived fast pyrolysis bio-oil (FPBO) and catalytic pyrolysis bio-oil (CPBO) was investigated with an upgrading approach using unsupported MoS2 catalysts generated in situ. Hydrodeoxygenation of FPBO and CPBO was evaluated in a continuous-flow reactor system using feed blends containing 18 wt% bio-oil in fuel oil. For FPBO, 92.9 % deoxygenation was achieved with 0.51 wt% O in oil products, resulting in low acidity (0.32 mg KOH/g), while 74.8 % deoxygenation was obtained for CPBO with 1.24 wt% O and 0.48 mg KOH/g acidity in oil products. The lower deoxygenation of CPBO suggests that oxygenates in CPBO are less reactive than those in FPBO. In both cases, low solid yields were observed from 1.2 to 2.0 g/100 g bio-oil. XRD and HRTEM detected few-layer stacked structure for the in-situ formed MoS2 catalysts. The oil product from CPBO retained more biogenic carbon than from FPBO, with the diesel fraction from CPBO exhibiting a higher biogenic carbon content and yield. Both diesel cuts meet almost all ASTM D975 specifications, except for S content, resulting from the high S/Mo feed ratio used in the tests. Evaluation results demonstrated great potential for producing specifications-conforming diesel fractions from FPBO and CPBO upgrading using unsupported MoS2 catalyst.